Self-perceived memory impairment and cognitive performance in an elderly independent population with age-related white matter changes. Issue 8 (12th December 2007) - Miranda, B; Madureira, S; Verdelho, A; Ferro, J; Pantoni, L; Salvadori, E; Chabriat, H; Erkinjuntti, T; Fazekas, F; Hennerici, M; O'Brien, J; Scheltens, P; et al.
Abstract : Objectives: To determine whether self-perceived memory impairment is associated with the severity of white matter changes (WMC) and is related to cognitive impairment. Methods: Data were drawn from the multinational Leukoaraiosis and Disability Study (LADIS), which investigates the impact of WMC on global functioning. WMC severity was rated using the Fazekas scale. Medial temporal lobe atrophy (MTA) was scored visually and mean values were calculated. The neuropsychological battery consisted of the Mini-Mental State Examination, a modified version of the VADAS-Cog, Trail making and Stroop tests. A question about self-perceived memory impairment was used as a measure for presence of memory complaints. Cognitive performance was analysed test-by-test and in three main domains: memory, executive functions and speed/motor control. The Geriatric Depression Scale (GDS) was used as a measure of depressive symptoms. Results: Six hundred and thirty-eight subjects were included in this study. No association was found between memory complaints and the severity of WMC. Subjects with memory complaints (n = 399) had a higher GDS score [t(637)  = −7.15; p<0.02] and performed worse on almost all cognitive tests and on the three cognitive domains. Multiple linear regression showed that the worse performance on the memory domain was associated with memory complaints independently of depressive symptoms, WMC severity and MTA (R 2  = 0.183; F = 17.09, β = −0.126; p<0.05). Conclusion: In a sample of non-disabled elderly subjects with WMC, self-perceived memory impairment is significantly associated with objective memory impairment independently of the WMC severity, depressive symptoms and MTA.